2014
DOI: 10.1080/10824669.2014.977104
|View full text |Cite
|
Sign up to set email alerts
|

A Bridge to Graduation for At-Risk Latino Males: A Case Study

Abstract: Changing demographics, low Latino graduation rates, and changes to education fundingnationally and locally-challenge society to develop innovative strategies to navigate transformations affecting public education. This article presents findings from a collaborative community-engaged evaluation of a dropout prevention program for at-risk male Latino students. Our mixed-methods evaluation finds that the program has had a positive overall impact on its participants. In particular, program participation was associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…This requires district leaders and local organizations to invest in changing the trajectory of students who are on the path toward juvenile or adult incarceration. I highlight an exemplar study by Behr et al (2014) who found that when alternative schools modify their culture to empower students and educators to interact in a positive manner, it results in an increase in college aspirations and knowledge for students and reduces the criminalization of their students through socioemotional-based counseling practices, external mentors, and cultural sensitivity and engagement.…”
Section: Discussionmentioning
confidence: 93%
“…This requires district leaders and local organizations to invest in changing the trajectory of students who are on the path toward juvenile or adult incarceration. I highlight an exemplar study by Behr et al (2014) who found that when alternative schools modify their culture to empower students and educators to interact in a positive manner, it results in an increase in college aspirations and knowledge for students and reduces the criminalization of their students through socioemotional-based counseling practices, external mentors, and cultural sensitivity and engagement.…”
Section: Discussionmentioning
confidence: 93%
“…Interventions have been developed to support Latinx students' academic success, and several of these programs have incorporated Latinx cultural values. A dropout-prevention program for at-risk Latinx students was found to have an overall positive impact on students (Behr et al, 2014). Findings indicated that program participation was related with an overall increase in grade point average, a higher probability of graduation, fewer failing grades, fewer behavioral referrals, and increased academic and career aspirations.…”
Section: Enhancing Latinxs' Academic Successmentioning
confidence: 95%